2018
DOI: 10.22146/ijc.21158
|View full text |Cite
|
Sign up to set email alerts
|

New Prenylated Stilbenes and Antioxidant Activities of <i>Cajanus cajan</i> (L.) Millsp. (Pigeon pea)

Abstract: New Prenylated stilbene derivatives, 3-hydroxy-4-prenyl-5-methoxy-stilbene acid (1) and 5,4'-dihydroxy-3-methoxy-2-prenyl-stilbene (2) Millsp.; stilben terprenilasi; antioksidan;2, ABSTRAK Dua turunan stilben terprenilasi baru, Asam 3-hidroksi-4-prenil-5-metoksi-stilben (1) dan 5,4'-dihidroksi-3-metoksi-2-prenil-stilben (2) telah berhasil diisolasi dari ekstrak metanol tumbuhan kacang kayu (Cajanus cajan (L.) Millsp.) anggota famili fabaceae. Tujuan penelitian ini adalah untuk mengetahui potensi senyawa-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These results suggest the presence of phenolic compounds could be major contributor to antioxidant activity. The phenolic compounds including xanthone [37] or stilbene [38] have been reported as a potent antioxidant activity. Based on this study, the phenolic compounds of C. odorata could be extracted by the polar and semipolar solvents very well.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest the presence of phenolic compounds could be major contributor to antioxidant activity. The phenolic compounds including xanthone [37] or stilbene [38] have been reported as a potent antioxidant activity. Based on this study, the phenolic compounds of C. odorata could be extracted by the polar and semipolar solvents very well.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47][48][49][50][51] New prenylated stilbene derivatives, 3-hydroxy-4-prenyl-5-methoxy-stilbene acid (116) and 5,4'-dihydroxy-3methoxy-2-prenyl-stilbene (117) had been isolated from methanol extract of Cajanus cajan (L.) Millsp. [52] At present, a number of resveratrol derivatives have been isolated and extracted from peanuts, trans-resvratrol, cis-resveratrol, trans-piced, cis-piceid, arachidin I, arachidin II, arachidin III (118-124), [53] cudrastilbene, 3,5,3'-trihydroxy-4'methoxy-5'-isopentenylstlbene, arahypin B, arahypin-13, arahypin-14, arahypin-15, arahypin-6, arahypin-7, arahypin-11, arahypin-12 (125-134). [54] Seven stilbene compounds (135-141) were isolated from Maackia hupehensis (135-141).…”
Section: Stilbenes Isolated From Leguminosaementioning
confidence: 99%
“…However, Cajanstilbenoid B (51) showed strong toxicity only against HepG2 (IC50 value: 5.99 µM) and A549 cells (IC50 value: 6.18 µM). [31] Cajanotone (52) and Cajanstilbene acid (54) showed strong cytotoxicity against A549 cells (with IC50 values of 5.9 and 4.4 µM , respectively), but moderate cytotoxicity against HepG2 and MCF-7 cell lines (with IC50 values from 12.2 to 17.9 µM), pinosylvin monomethyl ether (55) showed strong cytotoxicity against MCF-7 (with an IC50 value of 8.8 µM) and A549 (with an IC50 value of 7.4 µM) cell lines and moderate activity against HepG2 cells, with an IC50 value of 15.5 µM , [30] miyabenol C (80) exerted an inhibitory effect on protein kinasec in a non-competitive inhibition mode. [70] Miyabenol C (80) kobo-phenol A (82) and (+)-α-viniferin (84) could significantly inhibit the growth of A549 cells, and the effects of these compounds on the activities of egg autokinase c and isozymes in two human lung cancer cell lines (CA549 and HCI-H446) were studied.…”
Section: Antineoplastic Activitymentioning
confidence: 99%
“…For example, Chromolaena odorata is known as a potent antioxidant folk medicine in Ambon-Indonesia (Putri and Fatmawati 2019). Other natural antioxidants include Syzygium Polyanthum (Hidayati et al 2017), Moringa oleifera (Fitriana et al 2016), and Cajanus cajan (Ersam et al 2016). In addition, S. polyanthum (Ramadhania et al 2018) and Sonneratia ovate (Khumaidah et al 2018) are reported to be antibacterial, and Garcinia mangostana is known to act as an anti-diabetic agent (Fatmawati et al 2014).…”
Section: Introductionmentioning
confidence: 99%